Neonatal Outcomes in the MONEAD Study of Pregnant Women with Epilepsy - Linda J. Van Marter, MD, MPH; Page B. Pennell, MD; Carrie Brown, MS; Adam L. Hartman, MD; Ryan C. May, PhD; Thomas McElrath, MD, PhD; Dominic Ippolito, MS; Kimford J. Meador, MD; Anto Bagic, MD; Gregory Barkley, MD; Jennifer Cavitt, MD; Jennifer DeWolfe, MD; et al. (Elsevier, 2021)
Objective: To determine whether growth measures at birth differ between offspring of pregnant women with epilepsy and healthy pregnant women. Study design: The Maternal Outcomes and Neurodevelopmental Effects of Antiepileptic Drugs (MONEAD) study is a National Institutes of Health-funded, prospective, observational, multicenter investigation of pregnancy outcomes for mothers and their infants. Between 2012 and 2016, pregnant women with epilepsy and healthy pregnant women were enrolled at 20 US epilepsy centers. Pregnant women with epilepsy were exposed to various antiepileptic drugs. The main outcome measure was small for gestational age at birth. Principal univariate and multivariate analyses compared outcomes between pregnant women with epilepsy and healthy pregnant women. Secondary analyses focused on outcomes among mothers receiving different antiepileptic drug therapies. Results: In total, 345 infants were born to 331 pregnant women with epilepsy and 106 infants were born to 102 healthy pregnant women. No differences were seen between infants born to pregnant women with epilepsy vs healthy pregnant women in preterm births, major congenital malformations, 5-minute Apgar <6, special care nursery or neonatal intensive care unit admission, gestational age, or any growth measure. There was no difference in the rates of small for gestational age status among infants born to pregnant women with epilepsy vs healthy pregnant women; however, infants born to mothers receiving topiramate had lower birth weight z scores and lamotrigine higher birth weight z scores compared with other monotherapies. The greatest rate of special care nursery or neonatal intensive care unit admission was observed among those on oxcarbazepine monotherapy. Conclusions: Maternal treatment with antiepileptic drugs, overall, appears unassociated with adverse early neonatal outcomes. However, specific monotherapies appear to affect fetal growth with, on average, the greatest reduction in birth weight z score observed among infants born to pregnant women with epilepsy exposed to topiramate monotherapy. Trial registration: ClinicalTrials.govNCT01730170